Hak Masyarakat Adat - Zalsabillah, Annisa; Dahlan, Darnia; Anugrah, Abdi; Taqyuddin, Andi (Media Hukum Indonesia (MHI), 2024)
Constitutional recognition and protection of indigenous peoples remains recognized after the 1945 Constitution was amended, where this is regulated in Article 18B paragraph (2) and Article 28I paragraph (3) of the 1945 Constitution. Although there is constitutional recognition and protection of indigenous peoples, there are still two main problems that have not been resolved. First, the recognition of indigenous peoples is enforced with certain conditions, namely as long as the indigenous peoples still exist, develop in accordance with the progress of the times, and in accordance with the principles of the Unitary State of the Republic of Indonesia (NKRI). These conditions come from provisions in lower laws, and in practice often become obstacles in providing recognition and protection of the rights of indigenous peoples. The phrase "as long as they are still alive and in accordance with the development of society and the principles of NKRI" often causes the recognition of indigenous peoples to be trapped in debates about the indicators that must be met. In fact, several existing laws and regulations do not provide uniform indicators to interpret these constitutional conditions. Second, in the constitution, there are two terms introduced, namely Customary Law Community Unity (Article 18B paragraph 2) and Traditional Community (Article 28I paragraph 3). There is no further explanation regarding the differences between the two terms. Law No. 6 of 2014 concerning Villages tries to translate Article 18B paragraph (2) by introducing the term "customary village" as the equivalent of Customary Law Community Unity. However, the implementation of this law still causes problems, especially related to the recognition of the social unit of the customary community, where the term "customary community" cannot be fully accommodated in the concept of "customary village" introduced by the Village Law.